2019
DOI: 10.1002/pbc.27693
|View full text |Cite
|
Sign up to set email alerts
|

SFCE METRO‐01 four‐drug metronomic regimen phase II trial for pediatric extracranial tumor

Abstract: Objective To investigate the antitumor activity of a four‐drug metronomic chemotherapy (MC) regimen in relapsed/progressing pediatric extracranial solid tumors (EST). The primary objective was clinical benefit (complete response /partial response/stable disease [SD]) after two cycles of therapy (four months). Methods Patients aged ≥4 to 25 years with progressing EST and adequate organ function were eligible. Treatment consisted of an eight‐week cycle of oral celecoxib b.i.d., weekly vinblastine, and oral cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…30 The metronomic therapy concepts continuously use of low-dose chemotherapeutic, anti-angiogenetic and immunomodulating drugs, which is demonstrated to obtain a sustained antitumor effect through modulating the tumor microenvironment. 31 However, a recent randomized clinical trial showed that the metronomic chemotherapy only reached 3.5% ORR in progressive pediatric solid malignant tumors and did not prolong progression-free survival compared with placebo. 32 In a phase II study, apatinib combined with MC reached 54% ORR and 8-month PFS in patients with platinum-resistant or platinum-refractory ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…30 The metronomic therapy concepts continuously use of low-dose chemotherapeutic, anti-angiogenetic and immunomodulating drugs, which is demonstrated to obtain a sustained antitumor effect through modulating the tumor microenvironment. 31 However, a recent randomized clinical trial showed that the metronomic chemotherapy only reached 3.5% ORR in progressive pediatric solid malignant tumors and did not prolong progression-free survival compared with placebo. 32 In a phase II study, apatinib combined with MC reached 54% ORR and 8-month PFS in patients with platinum-resistant or platinum-refractory ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the median PFS was three months and depended on the diagnosis, in line with previous studies on metronomics in palliative care settings. 11,[17][18][19] Although the number of patients treated in this study is higher than in most metronomic pediatric trials, 9,10,15,17,23,26 the design of the study with the lack of cohort of patients with different type of diseases and phase 2 design (i.e., Simon 2 steps) does not allow us to formally demonstrate its activity or absence of activity in specific tumors. Nevertheless, as reported in previous studies, our osteosarcoma patients were not good responders to metronomic chemotherapy.…”
Section: F I G U R Ementioning
confidence: 96%
“…Nevertheless, as reported in previous studies, our osteosarcoma patients were not good responders to metronomic chemotherapy. 11,17 Therefore, we do not believe that patients with osteosarcoma should be treated with this MC protocol. Conversely, some tumors such as neuroblastoma or lymphoma or low-grade glioma are good candidates for MC.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Two different areas of research can be identified: mCHT as maintenance treatment in different pediatric cancer [ 109 ] Metronomic combination of different chemotherapy drugs [ 110 , 111 ] mCHT in combination with other drugs [ 112 , 113 , 114 ] …”
Section: Metronomic Chemotherapy: Areas Of Noveltymentioning
confidence: 99%